The Right to Be Ill: Refusal Of Medical Treatment v. Public Health In a Democracy - Schultz, David (Medicine, Law & Society, 2023)
Debates regarding health and health care generally involve questions regarding whether there is a right to -either. But in a democracy do individuals have a right to refuse medical treatment? The 2019 Covid pandemic raised this question as democracies sought to balance individuals with medical mandates such as the wearing of masks or vaccines. This article examines that question asking whether there is a right to be ill and to refuse force medical treatment in the case of infectious diseases that are life threatening. The article will conclude that in most cases competent adults have a right to refuse medical treatment and be ill, yet such a right has to be balanced against a host of factors supporting the preservation of the life of others.